Chromatin-bound nuclear pore components regulate gene expression in higher eukaryotes - Capelson, Maya; Liang, Yun; Schulte, Roberta; Mair, William; Wagner, Ulrich; Hetzer, Martin W (Cell, 2010)
Nuclear pore complexes have recently been shown to play roles in gene activation; however their potential involvement in metazoan transcription remains unclear. Here we show that the nucleoporins Sec13, Nup98, and Nup88, as well as a group of FG-repeat nucleoporins, bind to the Drosophila genome at functionally distinct loci that often do not represent nuclear envelope contact sites. Whereas Nup88 localizes to silent loci, Sec13, Nup98, and a subset of FG-repeat nucleoporins bind to developmentally regulated genes undergoing transcription induction. Strikingly, RNAi-mediated knockdown of intranuclear Sec13 and Nup98 specifically inhibits transcription of their target genes and prevents efficient reactivation of transcription after heat shock, suggesting an essential role of NPC components in regulating complex gene expression programs of multicellular organisms.